Women's hormonal status and mate value influence relationship satisfaction and perceived male attractiveness - Hromatko, Ivana (Array, 2006)
Numerous findings suggest that female preferences for certain features of male faces vary during the menstrual cycle. Similarly, the changes during the cycle have also been found in women's commitment to a current relationship. Furthermore, from the perspective of securing benefits from extra-pair affairs, the differences between women with high vs. low mate value could be expected. In this study we have tried to connect these sets of findings: first, we explored differences between partnered and single women in their ratings of male facial attractiveness, in different phases of the menstrual cycle ; and second, their satisfaction with the current relationship in relation to the cycle phase and self-perceived mate value. Two groups of women (single vs. partnered) rated the attractiveness of two sets of male faces (normal vs. symmetrical). Repeated measures ANOVA showed that women in a relationship gave higher ratings of attractiveness for both normal and symmetrical faces, in luteal compared to early follicular phase of cycle, while single women showed the opposite pattern. Analyses of satisfaction with their current relationship in relation to cycle phase and self-perceived mate value showed that women with higher mate value are generally more satisfied with their current partners, and show smaller differences in satisfaction in various phases of the cycle. The results are interpreted in terms of content-specificity of hormone mediated adaptive design.